Disentangling succession and entrepreneurship gender gaps: gender norms, culture, and family - Feldmann, Manuel; Lukeš, Martin; Uhlaner, Lorraine M. (Small business economics, 2020)
This study adapts a multi-level view of culture, including society- and family-based gender norms and the family embeddedness perspective, to predict the career status of a sample of 2897 young Europeans (aged 18-35) from 11 countries, with at least one self-employed parent. We find that gender identity is associated with career status such that a woman is more likely than a man to be an employee vs. a successor to a family firm but no less likely to be a founder as compared with either being an employee or successor. However, certain family and society-level culture variables combined with gender identity reverse these trends. A woman with caring responsibilities is more likely to be a successor than either a founder or employee. Also, while two-way interaction effects for traditional gender norms and having a self-employed mother are weak or not significant, the study finds that in combination, a woman reporting both traditional gender norms and having a self-employed mother is more likely to be a successor than being either an employee or a founder, reversing gender identity main effects. Incorporating the family embeddedness perspective and the role of culture in occupational choice, we develop a better view of the gender gap in entrepreneurship, finding that the family may serve as a stronger influence than society when implied norms of these two levels of culture clash. By examining actual rather than intended career choice, we also contribute to the occupational choice literature on youth employment.